Financial performance analysis of LP Gas Ltd. with special reference to govt. restriction on new piped gas connection to households - Md. Asaduzzaman (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2015)
Link to publisher's homepage at http://ijbt.unimap.edu.my/